The Difficulties of English Department Students at Universitas Negeri Padang in Answering Reading Section of TOEFL - Risa Asrida; Fitrawati Fitrawati (Journal of English Language Teaching, 2019)
This research aimed to find out the students’ difficult skills in answering reading section of TOEFL. The participants of this study were 26 students at English department in 2016 academic years. This study used proportional stratified sampling to choose the sample. The instrument used in this research was reading TOEFL test. The test consisted 50 questions multiple choice with 55 minutes. The study found that the last year English students of Universitas Negeri Padang had problems in 13 skills among 5 topics assessed. There were five most difficult items; main idea questions, stated detail questions, transition questions, context to determine meaning of simple words, and determine the tone of the passage.